Ahp approach for material management operation in a cutting edge electronics design manufacturing company - Wapee Manopiniwes (2018)
The current paper is to study and obtain the most favorable criteria and sub-factors referred to the material management operations of the cutting edge electronics design manufacturing company in Thailand. The study is a complex problem involving qualitative and quantitative multi-criteria that has been considered in four main clusters consisting of Quality, Cost, Delivery and Productivity. A trade-off between these tangible and intangible factors is essential in selecting the most important factors. The Analytic Hierarchy Process (AHP) is applied in prioritizing the clusters and sub-factors with the pairwise comparison technique. The result of proposed framework indicates that can be applied to improve and assist decision-making in choosing the optimal factors combination for the company case study. © (2013) Trans Tech Publications, Switzerland.